Increased serum concentration of BAFF/APRIL and IgA2 subclass in patients with mixed connective tissue disease complicated by interstitial lung disease. Issue 2 (March 2014) - Kaneko, Toshiyuki; Amano, Hirofumi; Kawano, Shinya; Minowa, Kentaro; Ando, Seiichiro; Watanabe, Takashi; Nakano, Soichiro; Suzuki, Jun; Morimoto, Shinji; Tokano, Yoshiaki; Takasaki, Yoshinari
Abstract B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) are known to be crucial for B cell maturation and survival, and increased expression of these factors in various autoimmune diseases has been reported. Human B cells produce two IgA subclasses: IgA1 and IgA2, the latter being abundant in the distal intestine, saliva, colostrum and bronchial fluid. We investigated these parameters in patients with mixed connective tissue disease (MCTD) complicated by interstitial lung disease (ILD+), and compared them with those in MCTD patients without ILD (ILD−). Sixty-three MCTD patients were divided into two groups: 21 ILD+ patients and 42 ILD− patients. In each patient group we analyzed soluble BAFF/APRIL using ELISA, and IgA1 and IgA2 using double immunodiffusion. Furthermore, we analyzed BAFF–APRIL receptors, BCMA, BAFF-R and TACI, using flow cytometry. The ILD+ patients had significantly higher levels of BAFF/APRIL than the ILD− patients. There were significant correlations between BAFF/APRIL, BAFF/KL-6 and APRIL/KL-6. Although there was no significant inter-group difference in the serum IgA1 level, ILD+ patients had a significantly elevated IgA2 level in comparison with ILD− patients. Moreover, although there were no significant inter-group differences in the expression of BCMA, BAFF-R and TACI on B cells, the expression of BAFF-R was significantly decreased in the ILD+ patients. In recent years, relationships between BAFF/APRIL and IgA subclass have been reported. Our results suggest that an elevated level of BAFF/APRIL drives the maturation of B cells, subsequently leading to IgA2 class switching, and possibly to the development of ILD in patients with MCTD.